Measuring the Effectiveness of Online Learning: Experience, Achievement, and Absorption of Students in Higher Education - Octavia, Evi; Herawati, Shinta Dewi; Abdullah, Suji (Archives of Business Research, 2025)
This study aims to explore and understand the dynamics of responses and experiences of students and lecturers related to engagement behavior in the online learning process. Using qualitative methods and descriptive approaches, this study collected data through structured in-depth interviews with six participants. The findings of the study indicate positive and negative experiences influenced by various factors, such as student and lecturer personality, technology, and the environment. Negative experiences were more common in participants who had negative attitudes towards online learning and low emotional intelligence, which were often exacerbated by a lack of technical support, such as unstable networks, and limited interaction between lecturers and students. Difficulty in understanding the material and uninteresting content delivery were also obstacles. Conversely, positive experiences were found in participants who showed positive attitudes towards change, had good emotional intelligence, and received adequate support. This group tended to show high achievement, good understanding, and more positive experiences in online learning.